2022
DOI: 10.1002/ctm2.931
|View full text |Cite
|
Sign up to set email alerts
|

ISG15 deficiency features a complex cellular phenotype that responds to treatment with itaconate and derivatives

Abstract: Background Congenital ISG15 deficiency is a rare autoinflammatory disorder that is driven by chronically elevated systemic interferon levels and predominantly affects central nervous system and skin. Methods and results We have developed induced pluripotent stem cell‐derived macrophages and endothelial cells as a model to study the cellular phenotype of ISG15 deficiency and identify novel treatments. ISG15 –/– macrophages exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 77 publications
1
16
0
Order By: Relevance
“…Among the recent findings, the role of ISG15 as a regulator of cell metabolism stands out, both in mice and humans. In the past 6 years, several studies have demonstrated that ISG15 acts as a modulator of several pathways of cell metabolism and that its absence influences essential metabolic functions, such as OXPHOS and glycolysis ( 16 19 , 21 ). These novel functions of ISG15 are closely related to its well-established antiviral activity, as viruses depend on the metabolic features of the host to complete their infectious cycle ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the recent findings, the role of ISG15 as a regulator of cell metabolism stands out, both in mice and humans. In the past 6 years, several studies have demonstrated that ISG15 acts as a modulator of several pathways of cell metabolism and that its absence influences essential metabolic functions, such as OXPHOS and glycolysis ( 16 19 , 21 ). These novel functions of ISG15 are closely related to its well-established antiviral activity, as viruses depend on the metabolic features of the host to complete their infectious cycle ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was recently shown that in adipocytes, signaling through the interferon regulatory factor 3 (IRF3)/ISG15 axis results in the inhibition of glycolytic enzymes through ISGylation, strongly reducing oxygen consumption and thermogenic capacity ( 18 ). Of note, Waqas and colleagues ( 21 ) recently demonstrated that macrophages from patients who suffer congenital ISG15 deficiency display metabolic alterations that affect pathways such as mitochondrial respiration, glycolysis, amino acid metabolism, and redox balance, among others, highlighting the relevance of ISG15 as a regulator of cell metabolism also in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In a separate study with induced pluripotent stem cell-derived macrophages and endothelial cells as models, ISG15 −/− macrophages displayed the expected hyperinflammatory responses, but normal phagocytic function [75]. Their pathology included a range of dysregulated processes such as increased apoptosis/pyroptosis, oxidative stress and glycolysis, but decreased oxidative phosphorylation, β-oxidation, and NAD(P)H-dependent oxidoreductase activity [75].…”
Section: Isg15-dependent Metabolic Reprogramming and Mitochondrial Fu...mentioning
confidence: 99%
“…ISG15 −/− cells also displayed defective expression of genes involved in mitochondrial biogenesis and respiratory chain complexes II-V, resulting in diminished mitochondrial respiration. This phenotype was rescued upon reconstitution with wild-type ISG15, but only partially by a conjugation-deficient variant, suggesting that at least some of these phenotypes were driven by ISGylation to cellular targets [75]. Pharmacological treatment with itaconate and its derivatives, and the JAK1/2 inhibitor ruxolitinib could also reduce inflammatory responses, cell death, and oxidative stress [75].…”
Section: Isg15-dependent Metabolic Reprogramming and Mitochondrial Fu...mentioning
confidence: 99%
See 1 more Smart Citation